A glial cell line-derived neurotrophic factor delivery system enhances nerve regeneration across acellular nerve allografts. (1st January 2016) - Tajdaran, Kasra; Gordon, Tessa; Wood, Mathew D.; Shoichet, Molly S.; Borschel, Gregory H.
Graphical abstract: Abstract: Acellular nerve allografts (ANAs) are used clinically to bridge nerve gaps but these grafts, lacking Schwann cells and therapeutic levels of neurotrophic factors, do not support regeneration to the same extent as autografts. Here we investigated a local drug delivery system (DDS) for glial cell line-derived neurotrophic factor (GDNF) controlled release to implanted ANAs in rats using drug-loaded polymeric microspheres (MSs) embedded in a fibrin gel. In a rat hindlimb nerve gap model, a 10 mm ANA was used to bridge a 5 mm common peroneal (CP) nerve gap. Experimental groups received DDS treatment at both suture sites of the allografts releasing GDNF for either 2 weeks or 4 weeks. In negative control groups, rats received no DDS treatment or empty DDS. Rats receiving nerve isografts served as the positive control group. The numbers of motor and sensory neurons that regenerated their axons in all the groups with GDNF MS and isograft treatment were indistinguishable and significantly higher as compared to the negative control groups. Nerve histology distal to the nerve graft demonstrated increased axon counts and a shift to larger fiber diameters due to GDNF MS treatment. The sustained delivery of GDNF to the implanted ANA achieved in this study demonstrates the promise of this DDS for the management of severe nerve injuries in which allografts are placed. Statement of Significance: This work addresses the common clinical situation in which a nerve gap is bridged using acellular nerve allografts. However, these allografts are not as effective in supporting nerve regeneration as the gold standard method of autografting. The novel local drug delivery system used in this study provides sustained and controlled release of glial cell line-derived neurotrophic factor (GDNF), one of the most potent neurotrophic factors, which significantly improves nerve regeneration following severe nerve injuries. Results from this research will provide a mean of improving nerve allografts with locally delivered GDNF. This strategy may lead to a novel "off the shelf" alternative to the current management of severe nerve injuries.